Isolation and Quantification of the Hepatoprotective Flavonoids From Scleromitron diffusum (Willd.) R. J. Wang With Bio-Enzymatic Method Against NAFLD by UPLC–MS/MS - Qin, Yuxi; Zhao, Baojin; Deng, Huifang; Zhang, Mengjiao; Qiao, Yanan; Liu, Qiling; Shi, Chuandao; Li, Yunlan (Frontiers in Pharmacology, 2022)
Flavonoids were the major phytochemicals against hepatic peroxidative injury in Scleromitron diffusum (Willd.) R.J. Wang with an inventive bio-enzymatic method by our group (LU500041). Firstly, the total flavonoids from Scleromitron diffusum (Willd.) R.J. Wang were extracted by reflux, ultrasonic, ultrasound-assisted enzymatic methods (TFH), and the bio-enzymatic method (Ey-TFH). Then 24 flavonoids compounds were isolated and quantified in the extracts by UPLC-MS/MS. Next, representative six differential compounds in Ey-TFH were further screened out by multivariate statistical analysis compared with those in TFH. In a further step, Ey-TFH presented a higher protective rate (59.30 ± 0.81%) against H2O2-damaged HL-02 hepatocytes than TFH. And 6 representative differential compounds at 8 and 16 μmol/L all exerted significantly hepatoprotective effects (p < 0.05 or p < 0.01). At last, the therapeutic action of Ey-TFH for nonalcoholic fatty liver disease (NAFLD) was processed by a rat’s model induced with a high-fat diet. Ey-TFH (90, 120mg/kg) had significantly ameliorated the lipid accumulation in the rats’ model. (p < 0.05). Meanwhile, Ey-TFH relieved liver damage. The levels of ALT, ALP, AST, LDH, and γ-GT in rats’ serum were also significantly reduced (p < 0.05 or p < 0.01). In addition to this, the body’s antioxidant capacity was improved with elevated SOD and GSH levels (p < 0.05) and down-regulated MDA content (p < 0.01) after Ey-TFH administration. Histopathological observations of staining confirmed the hepatic-protective effect of Ey-TFH.